Epigenetic dysregulation of GATA1 is involved in myelodysplastic syndromes dyserythropoiesis - Hopfer, Olaf; Nolte, Florian; Nowak, Daniel; Hofmann, Wolf-Karsten (European journal of haematology, 2012)
Myelodysplastic syndromes (MDS) are characterized by dyserythropoiesis resulting in anemia. This pathological hallmark is incompletely understood. Notch signaling has been linked to impaired erythropoietic and megakaryopoietic development of CD34+ progenitor cells, but its role in MDS is unclear. We have analyzed the transcriptional activity of Notch pathway elements and its association with the key erythroid factor globin transcription factor 1 (GATA1) and the apoptosis regulatory gene B-cell lymphoma-xl (BCLxl) in MDS. The methylation of GATA1 erythroid promoter CpG dinucleotides flanking cis-regulatory elements, including an N-box suppressor binding site for HES1 and a GATA-box binding site, was examined in normal and MDS erythropoiesis. We have generated a kinetic in vitro model of MDS erythropoiesis using CD34+ bone marrow cells from healthy donors (n = 7) and patients with MDS (low risk: RA/n = 6, RARS/n = 3; high risk: RAEB/n = 4, RAEB-T/n = 2). RNA expression of GATA1, BCLxl, DLK1, Notch1, HES1, and HERP2 was measured by real-time RT-PCR (qPCR). DNA methylation at seven CpG dinucleotides of the GATA1 gene promoter was quantitatively analyzed by pyrosequencing of bisulfite-treated genomic DNA at any specific time point. For the Notch pathway elements, no conclusive expression differences were found between MDS and normal erythropoiesis. But we found steadily up-regulated RNA expression of GATA1 and of BCLxl during late normal erythropoietic differentiation. In contrast, during MDS, erythropoiesis a loss of typical up-regulation of GATA1 and BCLxl was observed. Hypermethylation of CpG dinucleotides flanking the repressor HES1 binding site within the 5′ region of GATA1 was detected particularly during late MDS erythropoiesis. Interestingly, decremental GATA1 promotor methylation values were seen during normal erythropoiesis matching GATA1 RNA up-regulation. Our data show that the critical erythropoietic transcription factor GATA1 as well as the antiapoptotic molecule BCLxl fails to be normally up-regulated during MDS erythropoiesis. The higher residual 5′-GATA1 methylation values in MDS erythropoiesis but decremental loss thereof in normal erythropoiesis suggest a gene dose effect for GATA1 during erythropoiesis being finely tuned by CpG methylation. Its dysregulation may contribute to the ineffective erythropoiesis observed in MDS.